Interactions of star-like polyelectrolyte micelles with hydrophobic counterions - Fernandez-Alvarez, Roberto; Nová, Lucie; Uhlík, Filip; Kereïche, Sami; Uchman, Mariusz; Košovan, Peter; Matějíček, Pavel (Journal of colloid and interface science, 2019)
Hydrophobicity of a counterion has a profound effect on the interaction with polyelectrolytes similar to that of multivalency. Specifically, understanding this interaction in weak polyelectrolyte micelles might assist in developing nanocarriers for pH-controlled encapsulation and release. We used star-like weak polyelectrolyte micelles of polystyrene-block-poly(2-vinyl pyridine) (PS-P2VP) with fixed aggregation number as a model polyelectrolyte, and cobalt bis(1,2-dicarbollide) (COSAN) as a model hydrophobic anion. We used NMR to assess the mobility of the polymer segments in the presence of varying amounts of COSAN, and at varying protonation degrees of the polyelectrolyte. Same experiments with indifferent electrolyte (NaCl) were used as a control. Furthermore, we used coarse-grained simulations to obtain a detailed picture of the effect of hydrophobic counterions on the conformation of the micelles. A small amount of hydrophobic counterions causes morphological changes within the micelles, whereas a bigger amount causes precipitation. This was confirmed both in simulations and in experiments. Furthermore, adsorption of the counterions induces ionization of the collapsed segments of the polyelectrolyte. Although the COSAN/P2VP system is rather specific, the generic model used in the coarse-grained simulations shows that the observed behavior is a consequence of synergy of hydrophobic and electrostatic attraction between polyelectrolytes and hydrophobic counterions. Our study provides general insights into the molecular mechanisms of these interactions.
Keywords: Star-like polyelectrolyte; Anionic boron cluster compound; Weak polyelectrolyte; Ionization equilibrium; Micelle; Ionic surfactant